La madera auxiliar en la construcción y su huella ecológica; caso de la superficie de contacto de la tarima - Bianconi Bailez, María Susana (Acta Universitaria, 2011)
An alternative framework is designed, based on recycled material, to tend to diminish the irrational use of wood. Wood related problems in concrete construction in the State of Mexico are presented, and this issue is related to the illegal harvest of timber. The wood framework life cycle assessment is graphed and several parameters are compared between our proposed hybrid frame and the conventional one. This new design is proposed to mitigate the irrational use of timer in the making of daily concrete building in situ.
Keywords: Array; Array; Array; Array; Array